2016
DOI: 10.11648/j.ajls.20160406.17
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Yam (<i>Dioscorea spp</i>.) Populations in South Western Region of Cameroon

Abstract: Yams are Dioscoreaceae grown in the tropics and sub-tropics and used as food and for related pharmaceutical properties. The South Western Region of Cameroon is a major yam producing zone. This study which evaluates morphological variability between ten linguistically different yam types grown in South Western Cameroon will serve as a necessary step for subsequent genetic study of the species. The yams, collected from nine sites, were planted in a completely randomized design in four locations. Analysis of data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…They are staple foods in many parts of the tropics, being the source of most of the daily carbohydrate intake for large populations [9,13]. These carbohydrates are mostly starches found in storage organs, which may be enlarged roots, corms, rhizomes, or tubers.…”
Section: Distribution and Abundance Of Yamsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are staple foods in many parts of the tropics, being the source of most of the daily carbohydrate intake for large populations [9,13]. These carbohydrates are mostly starches found in storage organs, which may be enlarged roots, corms, rhizomes, or tubers.…”
Section: Distribution and Abundance Of Yamsmentioning
confidence: 99%
“…These carbohydrates are mostly starches found in storage organs, which may be enlarged roots, corms, rhizomes, or tubers. Many types of yams are grown as traditional foods or are adapted to unique ecosystems and are of little importance to world food production [13]. The edible yams (Dioscorea alata, Dioscorea bulbifera and Dioscorea abyssinica) were important to the agriculture and food security of the in the community of the Sheko district even to other woreda of the Bench Maji Zone and many countries of the world that accounted the overall component of the diet for 2.2 billion people in developing countries [7,8].Among the finding of yams (Dioscorea spp.)…”
Section: Distribution and Abundance Of Yamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been carried out on yam using morphological descriptors [6][7][8][9]. Many authors [10][11][12][13] have reported the effectiveness of morphological markers in assessing genetic diversity in D. alata.…”
Section: Introductionmentioning
confidence: 99%
“…Yam ( Dioscorea spp.) is a multi‐species monocotyledonous tuber crop predominantly cultivated in the tropical regions of Africa, Southeast Asia, and Latin America (Azeteh et al., 2019; Darkwa, Olasanmi, et al., 2020; Oben et al., 2016). Dioscorea encompasses about 600 species (Burkill, 1960), of which only 11 are widely cultivated species (Darkwa, Olasanmi, et al., 2020).…”
Section: Introductionmentioning
confidence: 99%